Using the Resist‐Accept‐Direct management framework to respond to climate‐driven transformations in marine ecosystems. (19th March 2022) - Rogers‐Bennett, Laura; Yang, Gabrielle; Mann, Jordan D.
Abstract: Climate change is impacting natural ecosystems and the services they provide at an unprecedented rate, yet management is not keeping pace with radical ecosystem transformations. Management in marine systems is primarily designed to regulate fishing pressures, which may be of limited use in addressing large‐scale climate impacts. The Resist‐Accept‐Direct (RAD) is a flexible, novel framework that gives managers a way to structure and plan how to respond to radical shifts/transformations in ecosystems. We present marine case studies of broad scale impacts and outline how the responses may fit into the RAD concept. We use the RAD framework to address the collapse of the kelp forest in northern California and examine how potential policy guiding restoration strategies can be organised. We conclude that the response to most marine ecosystem transformations has been to use the resist strategy that includes adaptive management, and we suggest that for the kelp forests in California the resist strategy provides the best option for moving forward. The RAD framework will be useful for marine ecosystem transformations in which systems have reached their tipping points and now require novel restoration tools and thinking as we face climate change stressors and an unpredictable future.